1981
DOI: 10.1063/1.442394
|View full text |Cite
|
Sign up to set email alerts
|

Tests of approximation schemes for vibrational energy levels and partition functions for triatomics: H2O and SO2

Abstract: The accuracy of second order perturbation theory for multiply excited vibrational energy levels and partition functions for a symmetric top molecular ion J. Chem. Phys. 98, 4948 (1993); 10.1063/1.464950 Semiclassical vibrational eigenvalues of triatomic molecules: Application of the FFT method to SO2, H2O, H+ 3, and CO2 J. Chem. Phys. 81, 2394 (1984); 10.1063/1.447939 Coupled equations applied to the photodissociation of linear triatomics: A test of approximate schemes for calculating the line shape and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 15 publications
0
61
0
Order By: Relevance
“…We attribute this to neglect of bend-stretch interactions, which are expected, based on previous work 47 , 48 to be very important for Cartesian vibrations but relatively unimportant when bends are treated as occurring along curvilinear bend coordinates with fixed bond lengths. In particular, our previous experience with Cartesian and curvilinear vibrational coordinates for potential energy surfaces 47 and partition functions 48 of bound triatomics showed that when mode-mode coupling is neglected, as it is here and as it is often required in many other applications for practical reasons, the curvilinear bend coordinate leads to much better results than the Cartesian one.…”
Section: Vresultsmentioning
confidence: 89%
“…We attribute this to neglect of bend-stretch interactions, which are expected, based on previous work 47 , 48 to be very important for Cartesian vibrations but relatively unimportant when bends are treated as occurring along curvilinear bend coordinates with fixed bond lengths. In particular, our previous experience with Cartesian and curvilinear vibrational coordinates for potential energy surfaces 47 and partition functions 48 of bound triatomics showed that when mode-mode coupling is neglected, as it is here and as it is often required in many other applications for practical reasons, the curvilinear bend coordinate leads to much better results than the Cartesian one.…”
Section: Vresultsmentioning
confidence: 89%
“…Anharmonic vibrational spectra have been calculated by means of the vibrational second-order perturbation theory (VPT2) [80][81][82][83][84][85][86], exploiting the fully automated generalized second-order vibrational perturbation (GVPT2) approach [87][88][89]. The anharmonic force fields have been computed at the DFT/aug-N07D level and additionally, the hybrid CCSD(T)/DFT approach [20,90,91] has also been used to evaluate anharmonic frequencies.…”
Section: Vibrational Spectra Computationsmentioning
confidence: 99%
“…On the contrary, consistent procedures can be derived from QM computations of vibrational properties beyond the harmonic approximation. Recently, exact solutions for the treatment of few active modes to the vibrational problem for a generic system has been proposed 55 and effective schemes to compute vibrational frequencies within the second order vibrational perturbative (VPT2) [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] or vibrational self-consistent field (VSCF) based [76][77][78][79][80][81][82][83][84][85] approaches have been developed and implemented. In particular, a general VPT2 framework to compute thermodynamic properties, vibrational energies and transition intensities from the vibrational ground state to fundamentals, overtones and combination bands 66,67,[86][87][88] has been developed in our group.…”
Section: Introductionmentioning
confidence: 99%